Long-term efficacy of afatinib in a patient with squamous cell carcinoma of the lung and multiple ERBB family aberrations: afatinib in ERBB+ lung squamous cell carcinoma. Issue 8 (September 2019) - Jian, Hong; Han, Yuchen; Yu, Yongfeng; Lu, Shun
Abstract : In the phase 3 LUX-Lung 8 study, the ERBB family blocker, afatinib, significantly prolonged progression-free survival and overall survival relative to erlotinib in patients with relapsed/refractory squamous cell carcinoma of the lung. We describe the case of a 53-year-old Asian male enrolled in LUX-Lung 8 who experienced long-term benefit from afatinib following failure of platinum-based chemotherapy. The patient received afatinib, and remained progression-free for 14.7 months according to investigator review. Overall survival was 17.7 months. Tolerability-guided dose adjustments helped facilitate long-term afatinib use by mitigating drug-related adverse effects. Next-generation sequencing revealed that multiple genetic aberrations were present, including epidermal growth factor receptor copy number amplification, and mutations in ERBB4, ALK, RET, and BRCA2 . These findings may help to explain the enhanced response to afatinib and highlight the importance of biomarker analysis in guiding treatment decisions in patients with squamous cell carcinoma of the lung.